Lasting Effects of Surgically Used Topical Vasodilators on DIEP Artery Vascular Function - Kofoed, Jason S.; Tuncer, Fatma B.; Kwok, Alvin C.; Agarwal, Jayant P.; Ruple, Bradley A.; Borrelli, Marta; Symons, J. David; Richardson, Russell S.; Broxterman, Ryan M. (Journal of Reconstructive Microsurgery, 2024)
Background Surgeons routinely apply papaverine, lidocaine, or verapamil to produce acute vasodilation and prevent vasospasms during microvascular surgeries. There is evidence that topical vasodilators may induce postoperative endothelial and smooth muscle dysfunction, which would present after the acute vasodilatory effects of the topical drugs wear off. Therefore, the purpose of the current study was to evaluate the lasting effects of papaverine, lidocaine, and verapamil on human deep inferior epigastric perforator artery vasodilatory function after the acute effects of the topical drugs had worn off.Methods Deep inferior epigastric arterial samples were obtained from 12 patients during surgery. Each artery was dissected into four rings which where incubated for 1 minute in either physiological saline solution (control), papaverine (30 mg/mL), lidocaine (20 mg/mL), or verapamil (2.5 mg/mL), followed by a 2-hour washout. Endothelial-dependent and -independent vasorelaxation were then assessed by the isometric tension responses to acetylcholine or sodium nitroprusside, respectively.Results Peak acetylcholine-evoked vasorelaxation (mean ± standard deviation) was not different between control (62 ± 23%) and lidocaine (57 ± 18%, p = 0.881), but was reduced (all p < 0.002) in papaverine (22 ± 27%) and verapamil (22 ± 20%). Peak sodium nitroprusside-evoked vasorelaxation was not different (all p > 0.692) among control (132 ± 35%), lidocaine (121 ± 22%), and verapamil (127 ± 22%), but was less in papaverine (104 ± 41%; p = 0.045) than control.Conclusion Surgically used doses of papaverine and verapamil, but not lidocaine, have lasting negative effects on arterial vasodilatory function despite the acute effects of the drugs having worn off. These findings, in conjunction with the spasmolytic properties of each drug, may help guide the selection of an optimal topical vasodilator for use during microvascular surgeries.
Keywords: papaverine; verapamil; lidocaine